Audit Mutu Perguruan Tinggi: Analisis Literatur atas Implementasi dan Dampak Audit Mutu Internal dan Eksternal - Yusuf, M. (Kartika: Jurnal Studi Keislaman, 2026)
Internal Quality Audit (IQA) and External Quality Audit (EQA) are fundamental instruments in ensuring and improving the quality of higher education. Universities worldwide implement IQA and EQA as part of a sustainable quality assurance strategy to enhance global competitiveness. IQA plays a crucial role in conducting internal evaluations to identify areas requiring improvement, while EQA provides external validation of institutional quality. However, the implementation of these audits still faces various challenges, such as resource limitations, resistance to change, and differences in accreditation standards across agencies. Therefore, this study aims to analyze in depth the implementation of IQA and EQA in higher education through a systematic literature review. The research method involves an extensive review of various scholarly publications from reputable journals discussing quality audit practices. The findings indicate that the synergy between IQA and EQA enhances the effectiveness of quality assurance systems, strengthens accreditation outcomes, and bolsters institutional academic reputation. Moreover, an optimal quality audit implementation contributes to fostering a culture of continuous quality improvement in academic environments. The implications of this study highlight the importance of flexible, adaptive, and innovation-driven quality policies in supporting the continuous improvement of higher education institutions at an international level.